SKILL–BASED LEADERSHIP IN AVIATION INDUSTRY: A LEADERSHIP EFFECTIVENESS - Ariyanto, Denny; Nuur, Rangga Masyhuri (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2024)
This article aims to assess the effectiveness of leadership practices in enhancing organizational outcomes. Grounded in the principles of the skill approach framework, this study systematically identifies, synthesizes, and analyzes existing literature to unravel the intricate dynamics of leadership effectiveness in aviation contexts. The literature on leadership, aviation, and the skill approach is comprehensively reviewed through a rigorous search strategy encompassing academic databases, journals, and relevant sources. The Systematic Literature Review (SLR) methodology involves screening studies based on predefined inclusion criteria, followed by data extraction, synthesis, and quality assessment. Findings from the synthesized literature are analyzed to identify key themes, patterns, and relationships pertinent to skill-based leadership and its impact on organizational performance, safety culture, and crew dynamics within the aviation industry. By providing a structured and comprehensive synthesis of existing research, this review contributes valuable insights and evidence-based recommendations for leadership development initiatives and future research directions in the aviation sector.